2014
DOI: 10.1111/caim.12066
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Generation of Ideas: Virtual Idea Campaigns to Spur Creativity and Innovation

Abstract: International audienceFirms striving to maintain high rates of innovation need a continuous flow of new ideas. This is resulting in the establishment by large firms of IT platforms to generate ideas for innova- tion, and to encourage employees and customers to participate in innovation contests. However, there has been little published research on the use of IT platforms for idea genera- tion by employees, and it is unclear whether they facilitate in-house innovation. The purpose is to investigate how firms us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 35 publications
1
44
0
1
Order By: Relevance
“…Developing intervention research via a process of collaborative/action research seems consistent with recent methodological recommendations (e.g. Börjesson and Elmquist, ; Cirella, Guerci & Shani, ; Shani, Coghlan & Cirella, ; Elerud‐Tryde & Hooge, , Radaelli et al, ).…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…Developing intervention research via a process of collaborative/action research seems consistent with recent methodological recommendations (e.g. Börjesson and Elmquist, ; Cirella, Guerci & Shani, ; Shani, Coghlan & Cirella, ; Elerud‐Tryde & Hooge, , Radaelli et al, ).…”
Section: Introductionsupporting
confidence: 79%
“…Sung & Choi, ); and (v) technological support, including technical competencies, groupware and specific hardware/software (e.g. Elerud‐Tryde & Hooge, ).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…We approached the company – one of the top five designers of premium silk products for high‐end fashion labels and with over 100 years of history – and they agreed to work with us. Our early conversations with the CEO and his executive team led to the joint decision that an action research process, with, in particular, a collaborative orientation (Shani et al, ) and an insider/outsider team (Bartunek, ), was the best solution to act as the engine for a more rigorous and relevant research (e.g., Elerud‐Tryde & Hooge, ). Our initial meetings with the CEO and senior management indicated that encouraging learning and enhancing creativity would address an area of major ongoing challenges and concern.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, these studies have looked at the crowdsourcing marketplace, Amazon Mechanical Turk (www.mturk.com) and the internal crowdsourcing website IdeaStorm (www.ideastorm.com) (Bayus, 2013;Elerud-Tryde & Hooge, 2014;Hutter et al, 2011;Kittur, 2010;Ren, Nickerson, Mason, Sakamoto, & Graber, 2014;Sakamoto & Bao, 2011). Even though crowd ideation can be organized with explicit roles and rules, such as idea combination (Malhotra & Majchrzak, 2014;Wang, Wang, & Tao, 2017;Yu & Nickerson, 2011), in practice there are often few instructions for crowd interactions in ideation so that being exposed to others' ideas is a major interaction mechanism (Bayus, 2013;Luo & Toubia, 2015;Majchrzak & Malhotra, 2013;Moradian, Nasir, Lyons, Leung, & Sim, 2014;Siangliulue, Arnold, Gajos, & Dow, 2015).…”
Section: Introductionmentioning
confidence: 99%